(untitled) (The Pakistan Development Review, 1994)
In 1970 the book Industry and Trade in Some Developing Countries by myself, Tibor Scitovsky and Maurice Scott was published (referred to henceforth as LSS). It exposed the bad effects of the import substitution policies which had been the prevailing mode of industrialisation in developing countries for a long time. It advocated the elimination of quotas and a uniform tariff of 10-15 percent. The exchange rate should be adjusted to ensure that exports were competitive. If any industry was, exceptionally, to receive more promotion than that implied by the low tariff, this should be by some form of subsidisation which should not exceed another 10-15 percent of domestic value-added. LSS is, I believe, still the most quoted work on the subject. l It was quite closely related in theory to the methods of cost-benefit analysis proposed by Little and Mirrlees (1974) (referred to henceforth as LM). While the influence of LSS on the development literature was extensive, neither it nor LM would seem to have had any influence whatever on the policies of most developing countries for a decade. This is, perhaps, the normal fate of policyoriented books. Korea and Taiwan continued with the export policies they had already initiated. Admittedly these policies eliminated the bias against exports inherent in protective policies, a bias that LSS had castigated. But Korea, and to a lesser extent Taiwan, also reverted in the 1970s to the selective promotion of some mainly capital intensive industries (referred to as Heavy and Chemical Industiies (HCI) in Korea) producing tradables. In Korea, towards the end of the 1970s, it is possible that LSS played some part in the modification of the HCI drive. But only in Chile was the policy of a low uniform tariff, as advocated by LSS, wholly adopted. Chile has stuck to this policy.